Pengaruh Biaya Bahan Produksi, Biaya Pemasaran Dan Biaya Gaji Terhadap Profitabilitas Studi Kasus (Usaha Roti Bakery di Pangkalpinang: Deri Kusmadeni - Deri Kusma deni; Mohamad Makrus (Equity: Jurnal Ekonomi, 2022)
Abstact : Production costs are costs used in the production process consisting of direct raw materials and factory overhead costs. These production costs are also called product costs, which are costs that can be associated with a product, where these costs are part of the inventory. Marketing costs are all costs incurred in the context of marketing a product or merchandise, which costs arise from the time the product or merchandise is ready for sale until receipt of the sale proceeds into cash. Labor costs are costs incurred for workers or employees who can be physically traced into the manufacture of products and can also be traced easily or without consuming much expense. The problem Research is how the influence of the cost of production materials, marketing costs and salary costs on profitability, how the influence of the costs of production materials on profitability (ROA), how the influence of marketing costs on profitability, how the influence of salary costs on profitability (ROA). This Research purpose to determine the correlated of simultaneous costs of production materials, marketing costs and salary costs on profitability (ROA), partial correlated of production material costs, marketing costs and salary costs on profitability (ROA) Analysis of the data used in this research is multiple regression analysis, the coefficient of determination (R2) is 0.540 meaning that 54.0% of the variation in profitability can be explained by the variable costs of production materials, marketing costs and salary costs, while 46.0% from other factors not examined in this study. The F test results obtained the calculated F value of 12.522 is greater than the F table of 2.90 or a significance of 0,000 <α (0.05), the hypothesis states that the variable costs of production materials, marketing costs and salary costs correlated on profitability. Based on the t test that the variable costs of production materials and salary costs affect profitability while the variable marketing costs have no correlated on profitability Keywords: material production costs, marketing costs, salary costs, profitability